Heart failure with preserved ejection fraction after left‐sided valve surgery: prevalent and relevant. (4th October 2021) - Kammerlander, Andreas A.; Nitsche, Christian; Donà, Carolina; Koschutnik, Matthias; Dannenberg, Varius; Mascherbauer, Katharina; Schönbauer, Robert; Zafar, Amna; Winter, Max‐Paul; Bartko, Philipp E.; Goliasch, Georg; Hengstenberg, Christian; et al.
Abstract : Aims: To investigate the epidemiological and prognostic relationship between heart failure with preserved ejection fraction (HFpEF) and left‐sided valve surgery using all‐cause mortality as a primary endpoint. Methods and results: We studied a total of 973 patients, of whom 673 had undergone left‐sided valve surgery (time from surgery to enrolment 50 ± 30 months after valve surgery) and 300 patients with HFpEF without prior surgery served as control group. Among patients after surgery, 67.4% fulfilled all criteria of HFpEF according to current guideline recommendations, 20.6% had no heart failure (HF), and 12.0% had HF with mid‐range or reduced ejection fraction (HFmrEF/HFrEF). During 83 ± 39 months of follow‐up, a total of 335 (34.4%) patients died. Compared to surgical patients with no subsequent HF, patients with HFpEF and HFmrEF/HFrEF after surgery showed significantly higher all‐cause mortality rates [hazard ratio (HR) 1.80, 95% confidence interval (CI) 1.25–2.57, P  = 0.001; and HR 1.86, 95% CI 1.16–2.98, P  = 0.010, respectively]. This increased mortality rate was similar to the control HFpEF group without surgery (HR 2.05, 95% CI 1.38–3.02, P  < 0.001). Results remained consistent after adjustment for clinical and imaging risk factors and when using the established HFA‐PEFF risk score for HFpEF diagnosis. Notably, only 12.5% of HFpEF patients after surgery were diagnosed with HF despite regular follow‐up visits by board‐certified cardiologists. In contrast, 92.1% of HFmrEF/HFrEF patients after surgery were diagnosed correctly. Conclusions: Heart failure with preserved ejection fraction following left‐sided valve surgery is highly prevalent, associated with unfavourable outcomes, but rarely recognized.